An illustrated guide to lady beetles (Coleoptera: Coccinellidae) of the Indian Subcontinent. Part 3. Tribe Aspidimerini - Poorani, J. (Zootaxa, 2024)
The tribe Aspidimerini (Coleoptera: Coccinellidae) is entirely Asiatic in distribution and most of the known species are primarily aphidophagous and occasionally feed on mealybugs, scales, and whiteflies. This illustrated guide to 26 species in four genera of Asidimerini of the Indian subcontinent is presented with diagnostic descriptions and supporting illustrations, including genitalia, wherever available. Details of distribution, prey and plant associations, and seasonal occurrence are provided based on collections, label data and literature. Immature stages are illustrated for three species of Pseudaspidimerus Kapur and one species of Trigonocarinatus Huo & Ren. One new species, Aspidimerus dissimilis sp. n., is described from Arunachal Pradesh, Northeastern India. Cryptogonus bilineatus Kapur, 1948, and Cryptogonus bryanti Kapur, 1948 are transferred to Trigonocarinatus Huo & Ren, 2015 (new combinations). The following new specific synonyms are proposed (junior synonym listed first): Cryptogonus kapuri Ghorpade, 1974 (=Trigonocarinatus bryanti (Kapur, 1948)); Cryptogonus nepalensis Bielawski, 1972 and C. nepalensis bhutanensis Bielawski, 1979 (=Cryptogonus ariasi (Mulsant, 1853)) (new synonyms). An updated checklist of the tribe Aspidimerini of the Indian subcontinent is also provided.